The «electronic book» as an object of theoretical analyze in linguistics and lingvodidactic of higher school (Pedagogy of Higher and Secondary Education, 2013)
Zakharchuk-Dyuke O. О. The «electronic book» as an object of theoretical analyze in linguistics and lingvodidactic of higher school.In the article were analyzed various defining terms of «electronic book», highlight the advantages of electronic book of linear, justified the relevance of work of students with electronic book сlasses at the school in High society in the Bologna process.
Keywords: Bologna process; information society; electronic book; hypertext; multimedia